Optimalisasi Kompetensi Kepribadian Dan Profesionalisme Guru Pendidikan Agama Islam (PAI) Dalam Mengajar - Ali , M. Makhrus (LP3M STAI Ibnurusyd, 2022)
This study uses qualitative research with concept analysis, to determine what efforts can be made to improve the teaching quality of pai teachers by maximizing the fulfillment of teacher personality and professional competence. It is known that a teacher should be objective when in a school environment, so that students become more comfortable with the presence of the teacher. In addition to meeting the character in order to achieve personality competence, teachers must also have professionals at work. Professional here is defined as the fulfillment of the teacher's responsibilities as an expert in the field of teacher theory and practice. Experts in the field of theory means that he mastered the teaching material and in practice he was able to convey the material well to students. This is the concern of researchers, so that teachers can have the quality of personality competence and professionalism are optimal.